Long term outcome of trichiasis surgery in the Gambia. Issue 5 (15th April 2005) - Burton, M J; Bowman, R J C; Faal, H; Aryee, E A N; Ikumapayi, U N; Alexander, N D E; Adegbola, R A; West, S K; Mabey, D C W; Foster, A; Johnson, G J; Bailey, R L
Abstract : Background: Trichiasis surgery is believed to reduce the risk of losing vision from trachoma. There are limited data on the long term outcome of surgery and its effect on vision and corneal opacification. Similarly, the determinants of failure are not well understood. Methods: A cohort of people in the Gambia who had undergone surgery for trachomatous trichiasis 3–4 years earlier was re-assessed. They were examined clinically and the conjunctiva was sampled for Chlamydia trachomatis polymerase chain reaction (PCR) and general bacterial culture. Results: In total, 141/162 people were re-examined. Recurrent trichiasis was found in 89/214 (41.6%) operated eyes and 52 (24.3%) eyes had five or more lashes touching the globe. Corneal opacification improved in 36 of 78 previously affected eyes. There was a general deterioration in visual acuity between surgery and follow up, which was greater if new corneal opacification developed or trichiasis returned. Recurrent trichiasis was associated with severe conjunctival inflammation and bacterial infection. C trachomatis was detected in only one individual. Conclusions: Recurrent trichiasis following surgery is a common potentially sight threatening problem. Some improvement in the cornea can occur following surgery and the rate of visual loss tended to be less in those without recurrent trichiasis. The role of conjunctival inflammation and bacterial infection needs to be investigated further. Follow up of patients is advised to identify individuals needing additional surgical treatment.